The incorporation of international law rules in regulating safety of navigation and marine pollution prevention in straits used for international navigation: a study of Malaysia’s national law and policy / Mohd Hazmi Mohd Rusli - Mohd Rusli, Mohd Hazmi (2010)
Ever since the 1982 United Nations Convention on the Law of the Sea (LOSC) entered into force in 16 November 1994, it has always been regarded as the Constitution that governs matters pertaining to ocean governance. As a result, the LOSC has ended the multiplicity of practices of various nations of the world in empowering their sovereignty, exercising their sovereign rights and duties towards their maritime space. Malaysia became a signatory of the LOSC on December 12, 1982 and ratified it on October 14, 1996. During the third United Nations Conference on the Law of the Sea (UNCLOS III), as a state that borders the Strait of Malacca, Malaysia was among the States Parties that raised the issue of navigational rights of foreign vessels through straits used for international navigation. UNCLOS III eventually gave birth to the LOSC in which rules on navigation of foreign vessels through straits used for international navigation are set out in Part III. After ratifying the LOSC, Malaysia ratified other related international maritime conventions such as the International Convention for the Prevention of Pollution from Ships, 1973, as modified by the Protocol of 1978 relating thereto (MARPOL 73/78), the International Convention On The Control Of Harmful Anti-fouling Systems on Ships 2001(AFS) and many more. This study will look at the extent to which these international rules have been incorporated and integrated into Malaysia’s domestic legislation and policy on these matters.